The Effectiveness of a Primary Care Diabetes Education and Self‐Management Program in Ireland: A 6‐Month Follow‐Up Study - Clodagh Scannell; Tonya O'Neill; Anne Griffin (Endocrinology, Diabetes & Metabolism)
ABSTRACT Aims Self‐management education is recognised as an essential element of comprehensive diabetes care. This study aims to assess the impact of the DESMOND (Diabetes Education and Self‐Management for Ongoing and Newly Diagnosed) structured diabetes self‐management education programme administered by a registered dietitian in a primary‐care setting on key clinical indicators (HbA1c, weight and BMI) in participants who returned for the locally developed 6‐month follow‐up session. Methods A retrospective analysis was conducted of participants who attended the DESMOND 6‐h structured diabetes self‐management education programme and returned for the locally developed follow‐up programme during 2018 in the Midwest of Ireland. Paired sample t‐tests and McNemar chi‐square tests were used to assess any differences between baseline and 6 months post‐intervention. Results There were 66 participants, mean age of 63 years. At follow‐up, HbA1c was reduced by 6.45 mmol/mol (standard deviation (SD): 15.02 mmol/mol, p = 0.006). The number of participants below the 53 mmol/mol cut‐off increased from 52% at baseline to 71% at follow‐up (p < 0.001). A mean weight reduction of 1.4 kg (SD: 4.4 kg, p = 0.21) was found at follow‐up. Those in the overweight BMI category decreased from 30.2% to 26.4%, a clinically significant result. Conclusion Better glycaemic control and clinically significant improvements in BMI and weight were seen at 6 months among participants who attended the DESMOND program and returned for the locally developed follow‐up session. This supports the emerging evidence of the effectiveness of self‐management education for diabetes care. Further research is required to determine the optimal contact time and frequency of sessions required in order to sustain the observed improvement in clinical outcomes.